Electrostimulation improves plant growth and modulates the flavonoid profile in aeroponic culture of Scutellaria baicalensis Georgi - Grzelka, Kajetan; Matkowski, Adam; Ślusarczyk, Sylwester (Frontiers in Plant Science, 2023)
Scutellaria baicalensis Georgi is a valuable medicinal plant of the Lamiaceae family. The roots – Scutellariae baicalensis radix have been valued in traditional medicine of East Asia and are also listed in several pharmacopoeias, such as Chinese and European. These roots contain high amounts of flavones of rare structure with unsubstituted B-ring, such as baicalein, wogonin and their glucuronides – baicalin and wogonoside, respectively. These major constituents are responsible for high pharmacological activity, mainly anti-inflammatory, antiviral, antitumor as well as BDZ-receptors modulating. There is a fast-growing demand for both the crude drug and the individual flavonoids obtained from it. However, the variability of content and composition of flavonoids in the roots is significant and affects pharmaceutical use, whereas little is known about the influence of various factors on the root quality. In our experiments we use aeroponics to determine the effect of electroporation as an abiotic stressor on plant growth, development and root mass, as well as its metabolic profile. Results: Electroporation significantly impacts plant growth and accumulation of flavonoids, especially baicalein and wogonin depending on parameters of the treatment. Concentrations of aglycones were increased in at least half of the treated plants. Highest amounts (2.5-fold increase compared to Control) were documented after applying electrical field characterized by following parameters: E = 30 kV/cm, t = 100 μs, N = 10. In conclusion, electrostimulation is an innovative and efficient way to increase plant growth, yield and content of bioactive flavones found in the root, but fine tuning of the parameters, such as electrical field strength (E), length (t) and number (N) of impulses delivered are of great importance. It was also shown that cultivation of the experimental plants in aeroponics has a positive impact on their survival and development, while being sustainable and efficient horticultural practice.